The Role of Social Support for Women Entrepreneurs in Reducing Conflict to Increase Business Performance - Prabawanti, Benedicta Evienia; Rusli, Meika Syahbana (Indonesian Journal of Business and Entrepreneurship, 2022)
The government's efforts to accelerate economic growth in Indonesia are carried out by encouraging people to become entrepreneurs. Several studies conducted during the last 10 years show that the growth of entrepreneurship in a country cannot be separated from the participation and role of women. The purpose of this study was to determine the relationship between social support and business performance improvement of women entrepreneurs. This study found that social support has an important role, especially for women entrepreneurs, with social support provided to women, multiple role conflicts can be reduced. Women can do their job to the fullest, and still carry out their role as wives and mothers in the family. The social support provided to women entrepreneurs really helps them to be able to calmly do their jobs, build and develop their businesses. Increasing social support will reduce dual role conflicts and will have an effect on improving the business performance of women entrepreneurs. The managerial implications of the research are 1. Women as entrepreneurs (women's entrepreneurship) can find the various forms of social support needed to help them reduce the dual role conflicts that are often experienced by women's entrepreneurship 2. Women as entrepreneurs (women's entrepreneurship) can develop appropriate strategies to improve their business performance through the social support they receive.3. Women as business actors (women entrepreneurship) can find out what dual role conflicts will arise and affect their business performance when they do not get social support.Keywords: social support, women entrepreneurs, dual role conflict, business performance